2008
DOI: 10.1007/s10533-008-9242-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of root and sediment phosphatase activity to increased nutrients and salinity

Abstract: Wetlands of northern Belize, distributed along a salinity gradient, are strongly phosphorus limited and dominated largely by three species of emergent macrophytes: Eleocharis cellulosa, Cladium jamaicense, and Typha domingensis. We assessed changes in root and sediment phosphatase activities of each species to simultaneous changes of nutrients (N, P) and salinity in a mesocosm experiment. Phosphorus and nitrogen treatment eVects on both root and sediment phosphatase were highly signiWcant for all the species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
(57 reference statements)
2
19
0
Order By: Relevance
“…Higher phosphatase activites in Cladium and Eleocharis (Cyperaceae) than in Typha (Typhaceae) were reported previously (Kuhn et al. , 2002; Rejmánková & Macek, 2008). Cattails, grasses, floating‐leaved macrophytes, and mangroves consistently showed low activities of both enzymes (Fig.…”
Section: Discussionsupporting
confidence: 44%
“…Higher phosphatase activites in Cladium and Eleocharis (Cyperaceae) than in Typha (Typhaceae) were reported previously (Kuhn et al. , 2002; Rejmánková & Macek, 2008). Cattails, grasses, floating‐leaved macrophytes, and mangroves consistently showed low activities of both enzymes (Fig.…”
Section: Discussionsupporting
confidence: 44%
“…The activities of all hydrolytic enzymes investigated increased towards the centre of the peatland in parallel with the decline in nutrient concentrations, while the microbial biomass concentration per surface area declined. Enzymes involved in the cycling of phosphorus and nitrogen respond strongly to changes in the availability of these nutrients, both in mineral soils (Olander and Vitousek 2000;Allison et al 2007) and wetlands (e.g., Bragazza et al 2006;Rejmánková and Macek 2008;Penton and Newman 2008), indicating a shift in resources allocation to increased enzyme activity to maintain metabolic rates. Similar rates of phosphatase activity were also reported from Malaysian peat swamps (Jackson et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…N limitation generally reduces leaf area development and increases biomass allocation to roots, whereas P‐limitation generally stimulates biomass turnover, nutrient resorption from senescing tissues and root exudate production (Ingestad & Agren 1991; Ryser, Verduyn & Lambers 1997; Treseder & Vitousek 2001; Güsewell 2005a,b). Some studies have suggested that the latter traits (those stimulated by P limitation) play an important role in determining which species dominate the vegetation under P‐limited conditions (Harrington, Fownes & Vitousek 2001; Miao 2004; Macek & Rejmánková 2007; Rejmánková & Macek 2008), but evidence supporting this idea has been limited so far, and there is no similar evidence that high biomass allocation characterizes species from N‐limited systems. This lack of evidence may be due to the fact that while numerous studies have compared species from more or less productive sites, only few have compared species from N‐and P‐limited sites.…”
Section: Introductionmentioning
confidence: 99%